Identification of cis-diols as intermediates in the oxidation of aromatic acids by a strain of Pseudomonas putida that contains a TOL plasmid. - Whited, G M (1986)
Pseudomonas putida BG1 was isolated from soil by enrichment with p-toluate and selection for growth with p-xylene. Other hydrocarbons that served as growth substrates were toluene, m-xylene, 3-ethyltoluene, and 1,2,4-trimethylbenzene. The enzymes responsible for growth on these substrates are encoded by a large plasmid with properties similar to those of TOL plasmids isolated from other strains of Pseudomonas. Treatment of P. putida BG1 with nitrosoguanidine led to the isolation of a mutant strain which, when grown with fructose, oxidized both p-xylene and p-toluate to (-)-cis-1,2-dihydroxy-4-methylcyclohexa-3,5-diene-1-carboxylic acid (cis-p-toluate diol). The structure of the diol was determined by conventional chemical techniques including identification of the products formed by acid-catalyzed dehydration and characterization of a methyl ester derivative. The cis-relative stereochemistry of the hydroxyl groups was determined by the isolation and characterization of an isopropylidene derivative. p-Xylene-grown cells contained an inducible NAD+-dependent dehydrogenase which formed catechols from cis-p-toluate diol and the analogous acid diols formed from the other hydrocarbon substrates listed above. The catechols were converted to meta ring fission products by an inducible catechol-2,3-dioxygenase which was partially purified from p-xylene-grown cells of P. putida BG1.